2021
DOI: 10.1002/pbc.29483
|View full text |Cite
|
Sign up to set email alerts
|

Changes in executive function in pediatric brain tumor survivors

Abstract: Objective: Pediatric oncology survivors are at risk for executive function (EF) and working memory (WM) deficits, which can be measured via performance-based measures or rating scales. Previous studies have shown these measurement methods to be weakly correlated. This study aimed to describe parent-rated EF and performancebased WM (PBWM) in pediatric brain tumor (BT) survivors, examine change in EF and PBWM across time, and investigate the relationship between parent-rated WM and PBWM. Method: The sample inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In another study, poor working memory has been observed among pediatric brain tumor patients, linking memory loss with primary brain tumor irrespective of the patient’s age [ 57 , 58 ]. Pediatric primary brain tumor survivors also show long-term working memory impairment after radiation and other therapeutic measures [ 59 , 60 ]. Among adult patients, neuropsychological evaluations reported major episodic memory loss with a primary brain tumor and continued even after resection of the tumor [ 61 , 62 ].…”
Section: Brain Tumors and Memory Loss: Common Links And Growing Evidencementioning
confidence: 99%
“…In another study, poor working memory has been observed among pediatric brain tumor patients, linking memory loss with primary brain tumor irrespective of the patient’s age [ 57 , 58 ]. Pediatric primary brain tumor survivors also show long-term working memory impairment after radiation and other therapeutic measures [ 59 , 60 ]. Among adult patients, neuropsychological evaluations reported major episodic memory loss with a primary brain tumor and continued even after resection of the tumor [ 61 , 62 ].…”
Section: Brain Tumors and Memory Loss: Common Links And Growing Evidencementioning
confidence: 99%